Surface Water Monitoring Using GIS and Remote Sensing applications: Case study in Bau Sau, Cat Tien National Park - Nguyen Thi Hoa; Vo Minh Hoan; Nguyen Thi Ha; Kieu Manh Huong (Journal of Forestry Science and Technology, 2024)
This study was conducted at Bau Sau, Cat Tien National Park, in Vietnam. Bau Sau is Vietnam’s second wetland site out of a total of 9 Ramsar sites that have been recognized by the Ramsar Convention Secretariat in Vietnam. The extraction of surface water is carried out in three methods, including object-based classification and the calculation of NDWI and MNDWI indices. After calculating the overall accuracy of all three methods, the method with the highest percentage will be chosen for extracting the surface water boundary for the study area. With an overall accuracy of 90%, the NDWI index was used for extracting the water surface map in the period 2015–2024. The results also showed that the surface water area in Bau Sau was 42.15 hectares in 2015, 41.89 hectares in 2020, and 41.51 hectares in 2024. The fluctuation in the surface water area during 2015-2024 is clearly visible, showing a decrease of 0.64 hectares. The fluctuation is attributed to the vegetation communities, with the proliferation of Cyperus cephalotes being the most notable. Cat Tien National Park managers need to pay attention and take early measures in the near future to avoid impacting the habitat of some animal species in this area.